An end to al-Qaeda destroying Bin Laden's jihad and restoring America's honor - Nance, Malcolm W. (St. Martin's Press, 2010)
Bin Laden has built a large following by perverting Islam to justify the mass murder of innocent people. By fighting him with bullets and bombs we have bolstered Bin Laden's recruiting efforts abroad, undermined civil liberties and economic security at home and tarnished America's reputation internationally. The author retools the "War on Terror" to assert that the U.S. could eliminate Al Qaeda in less than 24 months without a single violent military action, while recreating America's reputation as a force for good around the world. Nance's plan includes: dominating the information battlespace by exposing Al Qaeda to the rest of the international Moslem community as the global death cult that they are; waging a war against the fear Al Qaeda has stoked; drastically reducing the number of heavy military operations that cause the death of civilians in the process; and relying more heavily on counterintelligence to root out the terrorist group.